Colombia could broker historic global agreement to share genetic diversity’s digital wealth - Mattson, Sean (2024)
Article on the Alliance of Bioversity International & CIAT's website by Sean Mattson, with inputs from Michael Halewood, Claudio Chiarolla and Isabel Lopez Noriega, regarding one of the world’s most biologically diverse countries (Colombia) potentially helping to guide world leaders toward a functional agreement on sharing benefits from digital genetic sequence information (DSI) at the UN Biodiversity Conference in October 2024.